The Beatles' Politics. (18th September 2012) - Collins, Marcus
<x xml:space="preserve">Abstract</x> Research Highlights and Abstract This article argues that the Beatles did much to legitimise pop as a means of political expression, to devise organisational structures to support such political activity and to politicise those who produced and consumed pop music. critiques the Beatles' political motives, attitudes, techniques and accomplishments. explains why the Beatles' political development was a process of trial and error in which they sought out strategies and ideologies to their liking. explores how the Beatles' politicisation altered existing conceptions of politics and pop. This article argues that the Beatles were instrumental in bringing together the hitherto divergent and mutually uncomprehending realms of politics and pop. Though not innovative political theorists, the Beatles were inventive political strategists who rehearsed virtually every technique subsequently used by politicised musicians. They practised consciousness‐raising, lobbying, patronage, abstentionism and civil disobedience. They founded utopian institutions and considered the relative merits of anarchy, democracy and revolutionary socialism. The multitude of political strategies adopted by the Beatles testified to their difficulties in finding one congruent with their outlook and temperament. Furthermore, the anti‐authoritarianism which formed the one consistent aspect of their political worldview was simplistic and their solutions were correspondingly unrealistic. They nevertheless did much to legitimise pop music as a means of political expression, to devise organisational structures to support such political activity and to politicise those who produced and consumed pop.